Assessing Participation of Women in a Cervical Cancer Screening Program in Peru - Robles, S. C.; Ferreccio, C.; Tsu, V.; Winkler, J.; Almonte, M.; Bingham, A.; Lewis, M.; Sasieni, P. (2012)
OBJECTIVE: To assess systemic and individual factors influencing participation of women in a screening program for cervical cancer. METHODS: In November 2000, a new cervical cancer screening program was introduced in the Region of San Martin, Peru. A total of 107 683 women, ages 25-49, were eligible for screening. This report covers the initial period from program inception through 31 October 2003. We used data from the program information system to identify systemic factors and individual characteristics influencing women's participation. We conducted a three-step analysis: we assessed systemic factors at the level of micronetworks or group of health centers, we estimated the odds of being a new user (never screened or not screened in the past 5 years) according to sociodemographic characteristics, and we assessed how women learned about the availability of screening services while controlling for influential factors identified in previous analyses. RESULTS: During the 3-year period, 36 759 eligible women attended screening services, for a participation rate of 32.3%. While attendance varied by area and time period, the program attracted 12 208 new users. Health care micronetworks with available static screening services had higher participation. New users were more likely than regular users to have less education and to report low use of family-planning services. All other factors being equal, they were also more likely than regular users to hear about screening services from a health care provider. CONCLUSION: In this setting, the presence of and contact with health services played a role in increasing the participation in screening of women not previously screened or not screened in the past 5 years.